Biogenic transport of glyphosate in the presence of LDPE microplastics: A mesocosm experiment. (February 2019) - Yang, Xiaomei; Lwanga, Esperanza Huerta; Bemani, Akram; Gertsen, Hennie; Salanki, Tamas; Guo, Xuetao; Fu, Haimei; Xue, Sha; Ritsema, Coen; Geissen, Violette
Abstract: The accumulation of plastic debris and herbicide residues has become a huge challenge and poses many potential risks to environmental health and soil quality. In the present study, we investigated the transport of glyphosate and its main metabolite, aminomethylphosphonic acid (AMPA) via earthworms in the presence of different concentrations of light density polyethylene microplastics in the litter layer during a 14-day mesocosm experiment. The results showed earthworm gallery weight was negatively affected by the combination of glyphosate and microplastics. Glyphosate and AMPA concentrated in the first centimetre of the top soil layer and the downward transport of glyphosate and AMPA was only detected in the earthworm burrows, ranging from 0.04 to 4.25 μg g −1 for glyphosate and from 0.01 (less than limit of detection) to 0.76 μg g −1 for AMPA. The transport rate of glyphosate (including AMPA) from the litter layer into earthworm burrows ranged from 6.6 ± 4.6% to 18.3 ± 2.4%, depending on synergetic effects of microplastics and glyphosate application. The findings imply that earthworm activities strongly influence pollutant movement into the soil, which potentially affects soil ecosystems. Further studies focused on the fate of pollutants in the microenvironment of earthworm burrows are needed. Graphical abstract: Highlights: Glyphosate transport via earthworm galleries was investigated. Earthworm galleries were negatively affected by high level of glyphosate and microplastics. Glyphosate/AMPA was concentrated inside of earthworm burrows rather than that in outside. Glyphosate was mainly transported into deeper soil layers via earthworm galleries. Abstract : Glyphosate was mainly transported into deeper soil layers via earthworm galleries which were influenced by synergetic effects of microplastics and glyphosate application.